Therapeutic education of patients with Type 2 diabetes mellitus and high cardiovascular risk - E. A. Palferova; V. A. Orlov (Российский кардиологический журнал, 2007)
The real-world, out-patient potential of therapeutic education (ТЕ) among individuals with Type 2 diabetes mellitus (DM-2) and arterial hypertension (AH) was investigated. Provided physicians were interested and motivated to participate, the effectiveness of this ТЕ program was no less than that for DM and AH Schools. The method could be recommended as an addition to multidisciplinary, integrated management of such patients, or as an alternative, if no Schools are available.